Sustained Interleukin-1β Exposure Modulates Multiple Steps in Glucocorticoid Receptor Signaling, Promoting Split-Resistance to the Transactivation of Prominent Anti-Inflammatory Genes by Glucocorticoids - Pedro Escoll; Ismael Ranz; Norman Muñoz-Antón; Ana van-; Melchor Alvarez-Mon; Carlos Martínez-Alonso; Eva Sanz; Antonio de- (Hindawi Limited, 2015)
Clinical treatment with glucocorticoids (GC) can be complicated by cytokine-induced glucocorticoid low-responsiveness (GC-resistance, GCR), a condition associated with a homogeneous reduction in the expression of GC-receptor- (GR-) driven anti-inflammatory genes. However, GR level and phosphorylation changes modify the expression of individual GR-responsive genes differently. As sustained IL-1β exposure is key in the pathogenesis of several major diseases with prevalent GCR, we examined GR signaling and the mRNA expression of six GR-driven genes in cells cultured in IL-1β and afterwards challenged with GC. After a GC challenge, sustained IL-1β exposure reduced the cytoplasmic GR level, GRSer203 and GRSer211 phosphorylation, and GR nuclear translocation and led to selective GCR in the expression of the studied genes. Compared to GC alone, in a broad range of GC doses plus sustained IL-1β, FKBP51 mRNA expression was reduced by 1/3, TTP by 2/3, and IRF8 was completely knocked down. In contrast, high GC doses did not change the expression of GILZ and DUSP1, while IGFBP1 was increased by 5-fold. These effects were cytokine-selective, IL-1β dose- and IL-1R1-dependent. The integrated gain and loss of gene functions in the "split GCR" model may provide target cells with a survival advantage by conferring resistance to apoptosis, chemotherapy, and GC.